The Influence of Financial Ratio on Financial Distress Amidst the Israel Boycott Issue - Putri Wili Yustanti; Tutik Dwi Karyanti; Kenneth Pinandhito (Politeknik Negeri Semarang, 2025)
The focus of this study is to examine how financial distress is impacted by liquidity, profitability, cash flow, and sales growth in companies that are listed on the IDX and are impacted by the boycott of Israel. This type of research is quantitive research this study utilizes secondary panel data obtained from the financial statements (balance sheets and income statements) of Indonesian Stock Exchange (IDX)-listed companies impacted by the Israeli boycott issue during the period first quarter of 2023 to the third quarter of 2024. Purposive sampling was used for the sample process, and a logistic regression model was processed using SPSS. The findings demonstrated that financial distress is significantly impacted by profitability and liquidity. However, financial distress is not much impacted by cash flow or sales growth.